Unpatterned Bioactive Poly(Butylene 1,4-Cyclohexanedicarboxylate)-Based Film Fast Induced Neuronal-Like Differentiation of Human Bone Marrow-Mesenchymal Stem Cells - Morena, Francesco (Int J Mol Sci, 2020)
Herein, we present poly(butylene 1,4-cyclohexanedicarboxylate) (PBCE) films characterized by an unpatterned microstructure and a specific hydrophobicity, capable of boosting a drastic cytoskeleton architecture remodeling, culminating with the neuronal-like differentiation of human bone marrow-mesenchymal stem cells (hBM-MSCs). We have used two different filming procedures to prepare the films, solvent casting (PBCE) and compression-moulding (PBCE*). PBCE film had a rough and porous surface with spherulite-like aggregations (Ø = 10–20 μm) and was characterized by a water contact angle = 100°. PBCE* showed a smooth and continuous surface without voids and visible spherulite-like aggregations and was more hydrophobic (WCA = 110°). Both surface characteristics were modulated through the copolymerization of different amounts of ether-oxygen-containing co-units into PBCE chemical structure. We showed that only the surface characteristics of PBCE-solvent-casted films steered hBM-MSCs toward a neuronal-like differentiation. hBM-MSCs lost their canonical mesenchymal morphology, acquired a neuronal polarized shape with a long cell protrusion (≥150 μm), expressed neuron-specific class III β-tubulin and microtubule-associated protein 2 neuronal markers, while nestin, a marker of uncommitted stem cells, was drastically silenced. These events were observed as early as 2-days after cell seeding. Of note, the phenomenon was totally absent on PBCE* film, as hBM-MSCs maintained the mesenchymal shape and behavior and did not express neuronal/glial markers.